Bile acid toxicity in Paneth cells contributes to gut dysbiosis induced by high-fat feeding - Zhou, Hui (JCI Insight, 2020)
High-fat feeding (HFF) leads to gut dysbiosis through unclear mechanisms. We hypothesize that bile acids secreted in response to high-fat diets (HFDs) may act on intestinal Paneth cells, leading to gut dysbiosis. We found that HFF resulted in widespread taxonomic shifts in the bacteria of the ileal mucosa, characterized by depletion of Lactobacillus and enrichment of Akkermansia muciniphila, Clostridium XIVa, Ruminococcaceae, and Lachnospiraceae, which were prevented by the bile acid binder cholestyramine. Immunohistochemistry and in situ hybridization studies showed that G protein–coupled bile acid receptor (TGR5) expressed in Paneth cells was upregulated in the rats fed HFD or normal chow supplemented with cholic acid. This was accompanied by decreased lysozyme(+) Paneth cells and α-defensin 5 and 6 and increased expression of XBP-1. Pretreatment with ER stress inhibitor 4PBA or with cholestyramine prevented these changes. Ileal explants incubated with deoxycholic acid or cholic acid caused a decrease in α-defensin 5 and 6 and an increase in XBP-1, which was prevented by TGR5 antibody or 4PBA. In conclusion, this is the first demonstration to our knowledge that TGR5 is expressed in Paneth cells. HFF resulted in increased bile acid secretion and upregulation of TGR5 expression in Paneth cells. Bile acid toxicity in Paneth cells contributes to gut dysbiosis induced by HFF.